English Deutsch Français Italiano Español Português 繁體中文 Bahasa Indonesia Tiếng Việt ภาษาไทย
All categories

This is the problem:
(a^2)(a^x/2)(a^2)^x
Then, this is expression is divided by
(a^-3)^-x

The correct answer to the problem is :
a^2-x/2

I simply need to know how to arrive at the correct answer. :)

2007-05-15 04:35:36 · 3 answers · asked by chrizzle08 2 in Science & Mathematics Mathematics

3 answers

Take it step by step. In the numerator the last term is
(a^2)^x = a^2x
This leaves the numerator as the product of three things all with the same base of 'a' therefore just add all the exponents to get (a^2)(a^x/2)(a^2x) = a^(2 + (5x/2))
The denominator is (a^-3)^(-x) = a^(-3*-x) = a^3x
Now to divide numerator by denominator just subtract exponents to get
[a^(2 + (5x/2)] / a^3x = a^(2 + (5x/2) - 3x) = a^(2 - (x/2)).

Why on earth would someone involve logs?

2007-05-15 05:07:35 · answer #1 · answered by Anonymous · 0 0

Top line is a² X a^(x/2) X a^(2x)

= a ^(2 + x/2 + 2x)

Bottom line is a^(3x)

Upon dividing:-
a^(2 + x / 2 - x) = a^(2 - x / 2) as required.

2007-05-15 14:47:00 · answer #2 · answered by Como 7 · 0 0

((a^2)(a^x/2)(a^2)^x )/((a^-3)^-x)
=((a^x)(a^2x))/(a^3x)
= a^3x/a^3x
=1
ans. is 1

2007-05-15 11:38:54 · answer #3 · answered by patel n 2 · 1 1

fedest.com, questions and answers